ANALISIS KOMPETENSI TERJEMAHAN TIGA UNIT LINGUISTIK PADA MAHASISWA SEMESTER 4 PENDIDIKAN BAHASA INGGRIS FKIP UNISRI 2015 - -, Sumardiono (UNIVERSITAS SLAMET RIYADI, 2016)
This research aims at identifying how three linguistic unit; word, phrase, and clause is translatedby students and how is the translation quality of the students.The data were gained from three different text. They are then classified based on words, phrasesand clauses. In the analysis, the data which is in the form of words, phrases and clauses weredescribed how it was translated; what technique were applied and whether there was a shift ornot.There are some conclussion derived: at the level of words, established equivalent is the mosttechnique applied in oredinary words, while borrowing is applied in technical terms: at wordsand clauses there are no shift occured while in phrase level there are some shipt occured. Ingeneral translation are accurate at word and clause level while at phrases level translation areless accurate.